En el corazón de la Amazonia: identidades, saberes e religiosidades no regime das águas marajoaras - Pacheco, Agenor Sarraf (2009)
This work speaks of travel, routes and roots of populations of oral traditions marajoaras, holders of local knowledge, in contact with Western knowledge learned. Your time is located at the confluence of shared contacts, permitted or denied between fields and forests, surprised in writing and orally to chroniclers, religious, travelers, literary scholars, writers and other storytellers. The original motto of these crossings is part of the 1930s, when the Order of Augustinians Recollects in Madrid, took over direction of the Christian faith and began to address letters of a sacramental Catholicism in areas of large islands. The direction given by the Augustinians, to return to her missionary upset with the expulsion of religious orders at the Pombalino Consulate, enhanced memory of Father Antonio Vieira and brought the challenge to review the documentation produced by the regular features for understanding identity, knowledge and traditions native or in diasporas in the Heart of the Amazon. These discoveries raised the research boat to revisit previous cultural borders, networks of sociability and conflict cobbled by indigenous peoples, African, mixed in with groups intermediations in power this colonial period. Inspired by Cultural Studies with emphasis in Latin American thought, the plots of this text also presents the social place granted by Amazon historiography to the paradisiacal Marajó and the complex differences and similarities in d form of historical Marajós. Inside of chronicles, memories and reports made by the Augustinians in his pastoral experience with residents of the region, is visible buildings, guidelines, negotiations, loneliness and limits of life in that dynamic environments require the unknown island condition human foreign. So, systems of waters, spaces of fields and forests turned into weapons socio-cultural contacts, sometimes uneven, insurgents, involving marajoaras, religious, political and economic elites from the regional between the colony and emerging time today. At the heart of these meetings, and trade disputes in yesterday and today, universes of beliefs, rituals and wisdom are strongly followed in local activities of work, fights against diseases, battles against the adversities of life experiences and cultural practices as party, prayers, songs, dance, without losing sight of gimmicks, transgression, (in) tolerances for men and women agree marajoaras the reconfiguration and reaffirmation of their cultural identities afroindígenas